Pengaruh Metode Akupresur terhadap Lamanya Persalinan: A Systematic Review - Rima Labiibah Hannun; Finta Isti Kundarti; Rahajeng Siti Nur Rahmawati (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Duration of the birth process can be a factor in the emergence of complications in the mother and fetus if the fetus has not been born after 12 hours since the active phase of labor. The purpose of this systematic review is to determine the effect of the acupressure method on the duration of labor. The search for articles was carried out on the PubMed, ProQuest, ScienceDirect, and Wiley Library databases from January 2012 to January 2022 with the inclusion criteria of maternity mothers. The keywords used “Acupressure” AND “Duration of Labor”; “Acupressure” AND “Labor Duratin”. The results obtained 8 articles that match the inclusion criteria with 961 respondents. A total of 4 articles stated that acupressure could reduce the duration of the active phase of labor, 3 articles stated that acupressure could not reduce the duration of the active phase of labor, and 1 article stated that ear acupressure could reduce the duration of the active phase of labor, but body acupressure could not reduce the duration of the active phase of labor. The acupressure method can reduce the duration of the active phase of labor, so that it can be used as an alternative for women giving birth in the future. Further research can be carried out to develop research on the most effective type and duration of massage at one acupressure point to speed up the duration of labor.